SALINITY TOLERANCE OF CERTAIN FRESHWATER FISHES - Kasim, H Mohamad (Indian Journal of Fisheries, 2011)
To Rhinomiigil corsula (Hamilton) salinities below 12.25 %. (S) are notlethal at any temperature within the tolerance limit, in acute exposure from freshwater.The optimum temperatures from 26 to 30Â°C favour salinity tolerance. Lowtemperature is more detrimental than high, though this species has higher resistancetimes at low temperature. Sarotherodon mossambica Peters resists salinitybetter than common carp and freshwater mullet, Among carps, the common carpis highly tolerant to salinity, mrigal is the least tolerant and fringelipped carp isintermediate. Salinity acclimation in the fringelipped carp has enhanced only theresistance to salinity and there is no change in the tolerance level.